Screening a mushroom extract library for activity against Acinetobacter baumannii and Burkholderia cepacia and the identification of a compound with anti-Burkholderia activity - Rott Marc; Toce Joseph; Monte Aaron; Klett Tiffany; Engelbrecht Kathleen; Gebhardt Michael; Dunek Craig; Schwan William R; Volk Thomas J; LiPuma John J; Liu Xue-Ting; McKelvey Ronald (BMC, 2010)
Abstract Background Acinetobacter baumannii and species within the Burkholderia cepacia complex (BCC) are significant opportunistic bacterial pathogens of humans. These species exhibit a high degree of antibiotic resistance, and some clinical isolates are resistant to all currently available antimicrobial drugs used for treatment. Thus, new drugs are needed to treat infections by these species. Mushrooms could be a potential source for new drugs to treat A. baumannii and BCC infections. Methods The aim of this study was to screen a library of crude extracts from 330 wild mushrooms by disk diffusion assays for antibacterial activity against A. baumannii and Burkholderia cepacia in the hope of identifying a novel natural drug that could be used to treat infections caused by these species. Once positive hits were identified, the extracts were subjected to bioassay-guided separations to isolate and identify the active drug molecules. MICs were performed to gauge the in vitro activity of the purified compounds. Results Only three crude extracts (0.9%) had activity against A. baumannii and B. cepacia. Compounds from two of these extracts had MICs greater than 128 μg/ml, and further analyses were not performed. From the third extract, prepared from Leucopaxillus albissimus, 2-aminoquinoline (2-AQ) was isolated. This compound exhibited a modest MIC in vitro against strains from nine different BCC species, including multi-drug resistant clinical isolates (MIC = 8-64 μg/ml), and a weak MIC (128 μg/ml) against A baumannii. The IC50 against a murine monocyte line was 1.5 mg/ml. Conclusion The small number of positive hits in this study suggests that finding a new drug from mushrooms to treat Gram-negative bacterial infections may be difficult. Although 2-AQ was identified in one mushroom, and it was shown to inhibit the growth of multi-drug resistant BCC isolates, the relatively high MICs (8-128 μg/ml) for both A. baumannii and BCC strains suggests that 2-AQ is not suitable for further drug development in its current form.